Overview of Hemoglobin Levels in Construction Workers in Tanjungsari Village, Sukaresik District, Tasikmalaya Regency - Fauziah, Vina Sylvia; Istianah, Euis Tia; Wilujeng, Endang Octaviana (Mukhtabar Journal of Medical Laboratory Technology, 2024)
Background & Objective: Hemoglobin is a tetrametric protein that binds iron (Fe) compounds that have an important role in the body, namely transporting oxygen from the organs of respiration throughout the body, and exchanging it with carbon dioxide from peripheral tissues to be released through the organs of respiration. Hemoglobin levels can be influenced by several factors, one of which is moderate to heavy-intensity physical activity. This study aims to determine haemoglobin levels in construction workers. Method: This research is a descriptive study with a total sampling technique conducted in May 2023.  Respondents in this study were 35 construction workers. Sampling was carried out in Tanjungsari Village, Sukaresik District, Tasikmalaya Regency and the examination was carried out at the Hematology Laboratory of STIKes Muhammadiyah Ciamis. Measurement using the Cyanmethemoglobin method with the instrument used is a photometer. The examination results were processed and displayed in table format for narration. Result: This study found normal haemoglobin levels in 23 respondents (66%), and 12 respondents (34%) with abnormal or below-normal haemoglobin levels in construction workers. Conclusion: It can be concluded that the average results of haemoglobin levels in construction workers are normal. Future research is expected to research the relationship between working duration and haemoglobin in heavy workers.